A randomized controlled study on assessment of health status, depression, and anxiety in coal miners with chronic obstructive pulmonary disease following yoga training - Rajashree Ranjita; Sumati Badhai; Alex Hankey; Hongasandra R Nagendra (International Journal of Yoga, 2016)
Context: Psychological comorbidities are prevalent in coal miners with chronic obstructive pulmonary disease (COPD) and contribute to the severity of the disease reducing their health status. Yoga has been shown to alleviate depression and anxiety associated with other chronic diseases but in COPD not been fully investigated. Aim: This study aimed to evaluate the role of yoga on health status, depression, and anxiety in coal miners with COPD. Materials and Methods: This was a randomized trial with two study arms (yoga and control), which enrolled 81 coal miners, ranging from 36 to 60 years with stage II and III stable COPD. Both groups were either on conventional treatment or combination of conventional care with yoga program for 12 weeks. Results: Data were collected through standardized questionnaires; COPD Assessment Test, Beck Depression Inventory and State and Trait Anxiety Inventory at the beginning and the end of the intervention. The yoga group showed statistically significant (P < 0.001) improvements on all scales within the group, all significantly different (P < 0.001) from changes observed in the controls. No significant prepost changes were observed in the control group (P > 0.05). Conclusion: Yoga program led to greater improvement in physical and mental health status than did conventional care. Yoga seems to be a safe, feasible, and effective treatment for patients with COPD. There is a need to conduct more comprehensive, high-quality, evidence-based studies to shed light on the current understanding of the efficacy of yoga in these chronic conditions and identify unanswered questions.